National primary care audit in end of life care and ACP and recommendations for improvement. Issue 2 (1st June 2012) - Thomas, K; Corner, H; Stobbart-Rowlands, M
Abstract : This audit provided the largest national assessment of primary care end-of-life care provision, with areas for improvement. It assessed the provision of EOLC and use of ACP based on use of Palliative Care/GSF Registers in primary care. 502 GP practices in 15 PCTs (60% uptake) submitted data from 4, 500 patients for every death over a 2 month period. The GSF After Death Analysis (ADA) Audit Tool providing outcome data for individual patients, and compared with recommended best practice standards. More patients on the register were offered ACP discussions that those not on the register, although there was some confusion of terminology between ACP and usual care planning. Only 27% of patients who died were included on the palliative care register, of these 23% were non-cancer. Those on the register were more likely to receive well-coordinated care and offered ACP discussions. This snapshot provides an objective overview of current community end-of-life care, demonstrating key areas for further improvement. Patients on the register received, better coordinated care than those not on the register, and were more likely to have ACP discussions recorded. Only 25% patient deaths were on the register, suggesting a need for earlier recognition and better coordination. . Suggestions for improvement included better means of identifying patients for the register, particularly non-cancer patients, use of Next Stage GSF Training, a 'Find your 1% campaign', use of electronic triggers, local strategic ACP plans and communication skills training.